PEBANDINGAN PEMAHAMAN KONSEP ANTARA PENGGUNAAN MEDIA PROTO CIRCUIT SIMULATOR DAN VOLTSIM CIRCUIT SIMULATOR MENGGUNAKAN METODE LATIHAN SKILL DRILL MATERI LISTRIK DINAMIS PESERTA DIDIK KELAS XII IPA SMA 13 TAKALAR - Tanti, Hamdana; Suarti; Jafar, Andi ferawati (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This research aimed to evaluate students' conceptual understanding of dynamic electricity at SMA Negeri 13 Takalar by comparing the effectiveness of the Proto Circuit Simulator and Voltsim Circuit Simulator media, both implemented through the skill drill practice method. Utilizing a Posttest-Only Comparison Group Design, the study involved two classes selected via purposive sampling, designated as Experimental Group I (Proto Circuit Simulator) and Experimental Group II (Voltsim Circuit Simulator). Data were collected using a validated multiple-choice conceptual understanding test and subsequently analyzed using t-tests. The results revealed a significant difference in learning outcomes between the two groups; specifically, students taught with the Proto Circuit Simulator achieved an average score of 84.30, falling into the